2010
DOI: 10.1002/smll.201000144
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor‐Nanocrystals‐Based White Light‐Emitting Diodes

Abstract: In response to the demands for energy and the concerns of global warming and climate change, energy efficient and environmentally friendly solid-state lighting, such as white light-emitting diodes (WLEDs), is considered to be the most promising and suitable light source. Because of their small size, high efficiency, and long lifetime, WLEDs based on colloidal semiconductor nanocrystals (or quantum dots) are emerging as a completely new technology platform for the development of flat-panel displays and solid-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
169
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(171 citation statements)
references
References 110 publications
(122 reference statements)
2
169
0
Order By: Relevance
“…This property has motivated the use of QDs in photovoltaics, lasers, and light emitting diodes. [143][144][145] Optically excited electron-hole pairs in a QD generate a temporary electric dipole moment. 146 It was suggested that the electric field associated with this dipole may be strong enough to generate an action potential in neuronal cells.…”
Section: Qdsmentioning
confidence: 99%
“…This property has motivated the use of QDs in photovoltaics, lasers, and light emitting diodes. [143][144][145] Optically excited electron-hole pairs in a QD generate a temporary electric dipole moment. 146 It was suggested that the electric field associated with this dipole may be strong enough to generate an action potential in neuronal cells.…”
Section: Qdsmentioning
confidence: 99%
“…Driven by the demands for lighting and display with both low power consumption and perfect visual effect, various colloidal nanocrystals (NCs) based white‐light‐emitting diodes (WLEDs) have been explored 1. Compared with traditional metal‐chalcogenide NCs, halide perovskites NCs possess unique characteristics of wide color tunability via postsynthesis anion exchange and good photochemical stability even without shell coating 2.…”
Section: Introductionmentioning
confidence: 99%
“…As the next generation color converters, scattering--free/scattering-less colloidal semiconductor nanocrystals (NCs) have higher luminescence efficiency, larger molar absorptivity and color tunability in comparison with traditional phosphors [9][10][11][12], which have been proven as promising color converters for WLEDs [13][14][15]. Various NCs such as ZnCdS [16][17][18][19][20][21], CdSe [22][23][24][25][26], ZnCdSe [27], CuInS [28][29][30][31][32][33][34][35], and InP [36][37][38][39][40][41] NCs have been successfully applied in the fabrication of WLEDs to enhance the color properties of the device.…”
Section: Introductionmentioning
confidence: 99%